A Detailed Hierarchical Model of Psychopathology: From Individual Symptoms up to the General Factor of Psychopathology. (March 2021) - Forbes, Miriam K.; Sunderland, Matthew; Rapee, Ronald M.; Batterham, Philip J.; Calear, Alison L.; Carragher, Natacha; Ruggero, Camilo; Zimmerman, Mark; Baillie, Andrew J.; Lynch, Samantha J.; Mewton, Louise; Slade, Tim; et al.
Much of the knowledge about the relationships among domains of psychopathology is built on the diagnostic categories described in the Diagnostic and Statistical Manual of Mental Disorders ( DSM ), and relatively little research has examined the symptom-level structure of psychopathology. The aim of this study was to delineate a detailed hierarchical model of psychopathology—from individual symptoms up to a general factor of psychopathology—allowing both higher- and lower-order dimensions to depart from the structure of the DSM . We explored the hierarchical structure of hundreds of symptoms spanning 18 DSM disorders in two large samples—one from the general population in Australia ( n = 3, 175) and the other a treatment-seeking clinical sample from the United States ( n = 1, 775). There was marked convergence between the two samples, offering new perspectives on higher-order dimensions of psychopathology. We also found several noteworthy departures from the structure of the DSM in the symptom-level data.